Kinetic Plasma Turbulence Generated in a 3D Current Sheet With Magnetic Islands - Zharkova, Valentina; Xia, Qian (Frontiers in Astronomy and Space Sciences, 2021)
In this paper we aim to investigate the kinetic turbulence in a reconnecting current sheet (RCS) with X- and O-nullpoints and to explore its link to the features of accelerated particles. We carry out simulations of magnetic reconnection in a thin current sheet with 3D magnetic field topology affected by tearing instability until the formation of two large magnetic islands using particle-in-cell (PIC) approach. The accelerated particles of the same charge entering an RCS from the opposite edges are shown accelerated to different energies forming the `bump-in-tail' velocity distributions that, in turn, can generates plasma turbulence in different locations. The turbulence-generated waves produced by either electron or proton beams can be identified from the energy spectra of electromagnetic field fluctuations in the phase and frequency domains. From the phase space analysis we gather that the kinetic turbulence is mainly generated by accelerated particle beams, which are later found to evolve into a phase-space hole indicating the beam breakage. In a wavenumber space the spectral index of the power spectrum of the turbulent magnetic field near the ion inertial length is found to be -2.7 that is consistent with other estimations. The collective turbulence power spectra are consistent with the high-frequency fluctuations of perpendicular electric field, or upper hybrid waves, to occur in a vicinity of X-nullpoints, where the Langmuir (LW) can be generated by accelerated electrons with high growth rates, while further from X-nullponts or on the edges of magnetic islands, where electrons become ejected and start moving across the magnetic field lines, Bernstein waves can be generated. The frequency spectra of high and low-frequency waves are explored in the kinetic turbulence in parallel and perpendicular directions to the local magnetic field showing noticeable lower hybrid turbulence occurring between the electron's gyro- and plasma frequencies seen also in the wavelet spectra. Fluctuation of the perpendicular electric field component of turbulence can be consistent with the oblique whistler waves generated on the ambient density fluctuations by intense electron beams. This study brings attention to a key role of particle acceleration in generation kinetic turbulence inside current sheets.